Hubungan antara Bauran Pemasaran Kecap Bango dan Keputusan Pembelian pada Generasi Millenial di Kota Denpasar - LAILA, KUMIL; PARINING, NYOMAN; ANGGRENI, IGAA LIES (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2020)
The Relation between Bango Soy Sauce Marketing Mix and Purchase Decisions onMillennials Generation in Denpasar City Increasing the soy sauce business every year causes intense competition by producers, including Unilever with its flagship soy sauce product Bango. In recent years, the number of Bango ketchup consumers in the millennium is less than that of generation X. Consumer decisions in the purchase of Kecap Bango in the millennium are influenced by many factors, one of which is the marketing mix elements.This research was conducted by 100 millennial generation respondents in Denpasar City who aimed to find out the dominant marketing mix elements considered by the millennium generation in buying Bango soy sauce in Denpasar City and analyze the relationship between the marketing mix and purchasing decisions. This research used accidental sampling technique with purposive sampling method and analyzed using Rank Spearman correlation. The results of this study indicate that the distribution is an element of the marketing mix which is most dominantly considered by the millennial generation in buying Bango soy sauce. Marketing mix elements that have a significant relationship with purchasing decisions are product and distribution.Producers are expected to continue to maintain and even develop product quality, diverse features and attractive designs so that consumers still trust the product and the marketing target of Bango soy sauce is achieved. In addition, producers are expected to maintain and even expand distribution channels so that consumers can easily get Bango soy sauce and will not move to other brands.